The Dimension of Sincerity According To The Qur’an And Sunnah: The Key To Accepting Deeds - Rofi'i, Muhammad Arwani; Emilda, Puri; Rachmawati, Emilia (International Journal of Research, 2024)
This article aims to examine the dimension of sincerity (sincerity) in deeds according to the Qur'an and Sunnah, emphasizing the purity of intention, consistency in doing good, and independence from human praise. This study uses a qualitative method with textual analysis of relevant Qur'anic verses and hadiths. The findings show that sincerity encompasses relationships with both Allah and fellow humans, manifested through the concept of tawakkal (reliance on Allah) and fairness in social interactions. Sincerity in human relations creates an environment full of mutual understanding and compassion. In Islam, sincerity, derived from the Arabic word "khalasa" meaning purification, is about performing worship solely for Allah without seeking human praise. In the Qur'an, sincerity encompasses choice, purity from flaws, exclusivity, and the oneness of Allah. Sincerity is a prerequisite for the acceptance of deeds, prayers, and repentance, and it brings great benefits such as the acceptance of deeds, great rewards, and protection from satanic interference. Hadiths from Umar ibn al-Khattab, Abu Hurairah, and Abu Sa'id al-Khudri emphasize the importance of pure intentions. Sincerity helps in forming honest character, enhancing the quality of worship, social harmony, spiritual resilience, and work ethic. Understanding and applying sincerity supports individuals and communities to be responsible and have high integrity, hence the need to intensify education on sincerity for broad positive impacts.